Исторические повести: [для среднего школьного возраста] / Сергей Алексеев - Алексеев Сергей Петрович (Школьная библиотека, 2007)
Экземпляры: (20170505) / Инвентарный номер: 33630 / Цена: 61.40 / Сис.шифр: Р2 / Авт.знак: А 47 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6